Determination of Relationships between Dysmorphobia Tendency and Praise Seeking, Rejection Avoidance - Minako Ohmura (Selected Topics in Humanities and Social Sciences Vol. 8, 2021)
In this study, we examined the relationships between dysmorphobia tendency and praise seeking, rejection avoidance, and self-oriented perfectionism. Subjects were 311 female university students. We created a model in which self-oriented perfectionism mediates the effect of praise seeking and rejection avoidance in dysmorphobia tendency. The results showed that subjects with a stronger desire for praise seeking and rejection avoidance showed more appearance evaluation apprehension and obsessive concentration on appearance. The results also show that praise seeking enhances self-oriented perfectionism, which in turn reduces appearance evaluation apprehension. People with a desire to acquire positive evaluations seek perfection in themselves, but if the desire to achieve perfection becomes stronger, they seek perfection in areas that are unrelated to appearance, and obsession with physical appearance weakens. This study is a first step toward clarifying the source of dysmorphobia tendency in female adolescents, but further research is required.